2001
DOI: 10.1006/viro.2001.1091
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Characterization, and Phylogenetic Analysis of a Shrimp White Spot Syndrome Virus Gene That Encodes a Protein Kinase

Abstract: An open reading frame (ORF) that encodes a 715-amino-acid polypeptide was found in an 8421-bp EcoRI fragment of the shrimp white spot syndrome virus (WSSV) genome. The polypeptide shows significant homology to eukaryotic serine/threonine protein kinase (PK) and contains the major conserved subdomains for eukaryotic protein kinases. Coupled in vitro transcription and translation generated a protein having an apparent molecular mass of about 87 kDa according to sodium dodecyl sulfate-polyacrylamide gel electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 67 publications
4
34
0
1
Order By: Relevance
“…The earlier onset of transcription of vp15 (Fig. 1) could be regulated by this TATA-box, as in other WSSV genes which have been shown or are likely to be expressed early in infection (rr1, rr2, pk and dnapol) (Tsai et al, 2000a;Liu et al, 2001;Chen et al, 2002). The transcriptional start and stop sites of the vps were determined by 59 and 39 RACE.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The earlier onset of transcription of vp15 (Fig. 1) could be regulated by this TATA-box, as in other WSSV genes which have been shown or are likely to be expressed early in infection (rr1, rr2, pk and dnapol) (Tsai et al, 2000a;Liu et al, 2001;Chen et al, 2002). The transcriptional start and stop sites of the vps were determined by 59 and 39 RACE.…”
Section: Discussionmentioning
confidence: 72%
“…Probably part of the 59 end of the mRNAs is missing in these studies , because intact 59 ends of mRNA are rarely recovered from cDNA libraries. Polyadenylation of the WSSV genes rr1, rr2, pk and dnapol is, respectively, 12, 13, 16 and 17 nt downstream of the polyadenylation signal (Liu et al, 2001;Tsai et al, 2000a;Chen et al, 2002). All identified WSSV polyadenylation sites are within the range of regular polyadenylation in eukaryotic mRNAs, which is typically located 15 to 25 nt downstream of the sequence AAUAAA (Fitzgerald & Shenk, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the complete sequence of WSSV has recently been reported by Van-Hulten et al (2002). Marks et al (2003) reported that a VP-15 was the only major protein structure gene with a consensus TATA-box compared to VP-19, VP-24, and VP-28, in which the earlier onset of transcription of VP-15 could be regulated by this TATA-box, as in other WSSV genes which have been shown or are likely to be expressed early in an infection (Tsai et al, 2000;Liu et al, 2001;Chen et al, 2002). Van-Hulten et al (2002) stated that VP-15 is a very basic protein and resembles histone protein which functions as a DNA-binding protein in the WSSV nucleocapsid.…”
Section: Transcription Factor and Amino Acid Deduction Of Vp-15 Wssvmentioning
confidence: 99%
“…In 2000, two major structural protein genes of WSSV (VP28 and VP26) were identified (van Hulten et al, 2000a), followed by genes for ribonucleotide reductase, endonuclease, protein kinase and other structural proteins (van Hulten et al, 2000b(van Hulten et al, , 2002Witteveldt et al, 2001;Liu et al, 2001;Chen et al, 2002;Zhang et al, 2002). In 2001, the entire 305 kb genome sequence was reported Yang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%